Perancangan Enterprise Architecture Sistem Informasi Toko Buah Berbasis Website dengan Framework TOGAF ADM - Putri, Andini Wangsa; Saepudin, Sudin (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2024)
Technology has become an integral element in modern business transformation, and plays a key role in improving operational efficiency. Toko Aneka Buah Ciaul is a business in the field of service that provides various types of fruits located on Jalan R.A. Kosasih Ciaul Subang Jaya, Kec.Cikole Kota Sukabumi, West Java. This store is one of the business entities that has not implemented SI/IT thoroughly. In its business activities, it still uses conventional methods, namely in the process of buying fruit consumers directly come to the store and in recording finances, procurement, inventory, and sales the owner only relies on notebooks and calculators. Of course, in this problem, information systems can be used as a solution. So in this study the author designed a Website-based Toko Buah Information System Enterprise Architecture using the TOGAF ADM framework with a focus on Premliminary Phase, Architecture Vision, Business Architecture, Information System Architecture, and Technology Architecture customized based on needs. The results of this research are in the form of a blueprint that includes the process of designing the system and the resulting technology. This research is expected to be used as a reference for store owners in making systems, with the aim of increasing efficiency and simplifying business processes in the future.